2011
DOI: 10.1143/apex.4.075101
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Modulated Terahertz Radiation Using Combined Plasma and Mechanical Resonances in Double-Carbon-Nanotube Device

Abstract: We propose a resonant detector of terahertz radiation modulated by megahertz or gigahertz signals. The detector is based on mechanically floating carbon nanotubes (CNTs), suspended over an insulator. The device operation is associated with the excitation of both plasma and mechanical oscillations in CNTs resulting in an ac displacement current between them. This current plays the role of the detector output signal. Using the proposed device model, we find that the frequency dependence of the detector responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As in the case of QDs, nanotubes/CNTs can also be used for detection purposes with several ways as nanoantenna 71 , 83 , bolometers 84 and even by using their mechanical properties 85 . Furthermore, CNTs can be coated with bio-safe and biocompatible materials, like piezoelectric zinc oxide (ZnO), and be safely used as terahertz electromechanical nanoresonators 72 .…”
Section: Nanotechnology For Thz Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the case of QDs, nanotubes/CNTs can also be used for detection purposes with several ways as nanoantenna 71 , 83 , bolometers 84 and even by using their mechanical properties 85 . Furthermore, CNTs can be coated with bio-safe and biocompatible materials, like piezoelectric zinc oxide (ZnO), and be safely used as terahertz electromechanical nanoresonators 72 .…”
Section: Nanotechnology For Thz Imagingmentioning
confidence: 99%
“…Furthermore, simulations have shown that CNT antenna arrays have better performance than single CNTs, and optimal design for receivers can be achieved. Very recently a novel resonant detector of THz radiation based on mechanically floating CNTs was presented 85 . The detector consists of two electrically coupled single-wall-CNTs, which lie parallel over an insulator and are characterised by a proportional response of the plasma-mechanical resonance to the mechanical oscillation quality factor.…”
Section: Nanotechnology For Thz Imagingmentioning
confidence: 99%
“…[16,17,18]. Those devices incorporated a conductive mechanically floating cantilever [16], nanowire or a nanotube [17] suspended over the channel of high-electron-mobility transistor.…”
Section: Introductionmentioning
confidence: 99%
“…The THz demodulators exploiting combined plasma-mechanical resonance were first proposed in Refs. [16,17,18]. Those devices incorporated a conductive mechanically floating cantilever [16], nanowire or a nanotube [17] suspended over the channel of high-electron-mobility transistor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation